2015 International Conference on Advances in Computer Engineering and Applications 2015
DOI: 10.1109/icacea.2015.7164682
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on automation of Indian sign language

Abstract: Hearing impaired people uses signs to communicate with others. Just like verbally spoken languages, there is no universal language as every country has its own spoken language so every country has their own dialect of sign language and in India they uses Indian Sign Language (ISL). In the last few years, researchers take interest in the automation of ISL. Some attempts have been made in India and other countries. In this study we try to explore and analyze the work have been made with automation of sign langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lots of study has been done on sensor-based approaches like gloves, wires, helmets etc [4][5] [6]. But due to the disadvantage of wear it perpetually is not possible, consequently further work is concentrated on Image based approaches [1]. Some previous work has been done on image based approaches for hand gesture and sign recognition in the last few years [14].There has been various methodologies for gesture recognition like HMM(Hidden markov model) [15], ANN(Artificial neural network) [16], Eigen value based [17], perceptual color based [1][18].In [19] authors proposed gesture apperception algorithm using GMM and HMM.…”
Section: Literature Surveymentioning
confidence: 99%
“…Lots of study has been done on sensor-based approaches like gloves, wires, helmets etc [4][5] [6]. But due to the disadvantage of wear it perpetually is not possible, consequently further work is concentrated on Image based approaches [1]. Some previous work has been done on image based approaches for hand gesture and sign recognition in the last few years [14].There has been various methodologies for gesture recognition like HMM(Hidden markov model) [15], ANN(Artificial neural network) [16], Eigen value based [17], perceptual color based [1][18].In [19] authors proposed gesture apperception algorithm using GMM and HMM.…”
Section: Literature Surveymentioning
confidence: 99%
“…Examples of past initiatives and future trends when coping with sign languages are outlined. A temporal dynamics of the generation of sign and the analysis of sign language for ISL were outlined in Verma et al (2015). Bhuyan et al (2006) suggested a sign language recognition using the face and arm interface.…”
Section: Related Workmentioning
confidence: 99%